Workload, Compensation, and Discipline on the Performance of Food Producer Employees in Sidoarjo During the Covid-19 Pandemic: Beban Kerja, Kompensasi, dan Kedisiplinan Terhadap Kinerja Karyawan Produsen Makanan di Sidoarjo Pada Masa Pandemi Covid-19 - Nuzulita, Shela Felisya; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of workload, compensation and discipline on the performance of employees of PT. Surya Pratista Hutama Sidoarjo during the covid-19 period. The sample in this study were employees of PT. Surya Pratista Hutama Sidoarjo with a total of 70 employees, the method used in this study is a quantitative method, in order to perform multiple linear test calculations. Analysis using SPSS software. The results of this study indicate that partially and simultaneously workload, compensation, discipline affect the work productivity of employees of PT. Surya Pratista Hutama (SUPRAMA) Sidoarjo